Aplicación del test de findrisc para la detección del riesgo de diabetes mellitus tipo 2 y su relación con el estilo de vida en pacientes adultos en el sector lucha obrera, Babahoyo, periodo octubre 2019 – marzo 2020. - Santistevan Macías, Ariana Stefany (2020)
Type II diabetes mellitus (DM2) is defined as “a metabolic disorder that has a multiple etiology, which is characterized by chronic hyperglycemia which causes metabolic disturbances which are caused by excess carbohydrates, fats and proteins, resulting in a disorder in insulin segregation.” In the development of the present investigation, the Findrisc test was used as a tool, which was applied to the Lucha Obrera sector of the Babahoyo canton, obtaining results such as 53% have a high risk of diabetes, 12.8% very high , 15.1% moderate, 11.3% slightly moderate and 7.5% very low of a total of 132 inhabitants, another important fact is that most cases occur due to bad eating habits and sedentary lifestyle which originates A bad lifestyle. For all this it is proposed a guide that seeks to educate people about what diabetes is, its complications and how to improve eating habits.